Wernicke Korsakoff syndrome in a teenage female as a complication of COVID‐19 - Hannah Skok; Joseph Jabour; Joseph Betcher (Journal of the American College of Emergency Physicians Open)
Abstract Wernicke encephalitis (WE) is usually associated with alcohol use disorder and caused by a deficiency in thiamine. Classic findings include confusion, ataxia, and ophthalmoplegia. This case is a unique presentation of WE in a 14‐year‐old female related to prior coronavirus disease infection. She had persistent dysgeusia and developed thiamine deficiency. She presented with confusion, ataxia, and changes in speech. She had a prolonged hospitalization but was discharged to an inpatient rehab facility with persistent symptoms. It is prudent to include thiamine deficiency in the differential for patients with any symptoms of WE and a history of nutritional deficiency.